Are self-confidence and curiosity in studying biology related to achievement motivation? - Ade Suryanda; Erna Heryanti; Fairuz Khairunnisa (Master Program of Biology Education, Universitas Lambung Mangkurat, 2022)
In the 2013 curriculum students are required to be active in all learning activities. Through active learning that has been applied, students are expected to be able to explore deeper information about Biology material that has or has not been explained by the teacher. This attitude shows that students have curiosity which will then lead to self-confidence so that it encourages students to achieve good results. This study aims to determine the correlation between self-confidence in studying biology and curiosity (curiosity) with student achievement motivation. This research was conducted at SMAN 97 Jakarta in the even semester 2020/2021 academic year. The method used is a quantitative method through correlational studies. The sample used was 100 students taken from three classes of XI MIPA using simple random sampling technique. The data in this study were taken using three test instruments, namely: self-confidence test, curiosity test and student achievement motivation test. Most of the results obtained from the three tests are in the high category, with the percentage of confidence in studying biology by 62%, curiosity by 62% and student achievement motivation by 57%. Therefore, based on the results of the study, it was found that there was a positive correlation between self-confidence in studying biology and curiosity with student achievement motivation.AbstrakPada kurikulum 2013 siswa dituntut aktif dalam segala kegiatan pembelajaran. Melalui pembelajaran aktif yang sudah diterapkan, siswa diharapkan dapat mengeksplor informasi yang lebih dalam tentang materi Biologi yang telah ataupun belum dijelaskan oleh guru. Sikap tersebut menunjukkan bahwa siswa memiliki rasa ingin tahu yang kemudian akan memunculkan rasa percaya diri sehingga mendorong siswa untuk mencapai hasil yang baik. Penelitian ini bertujuan untuk mengetahui hubungan antara kepercayaan diri dalam mempelajari biologi dan rasa ingin tahu dengan motivasi berprestasi siswa. Penelitian ini dilaksanakan di SMAN 97 Jakarta pada tahun ajaran 2020/2021 semester genap. Metode yang digunakan adalah metode kuantitatif melalui studi korelasional. Sampel yang digunakan berjumlah 100 siswa yang diambil dari tiga kelas XI MIPA dengan menggunakan teknik simple random sampling. Data dalam penelitian ini diambil dengan menggunakan tiga instrumen tes, yaitu: tes kepercayaan diri, tes rasa ingin tahu dan tes motivasi berprestasi siswa. Hasil terbanyak yang diperoleh dari ketiga tes tersebut masuk dalam kategori tinggi, dengan presentase kepercayaan diri dalam mempelajari biologi sebesar 62%, rasa ingin tahu sebesar 62% dan motivasi berprestasi siswa sebesar 57%. Oleh karena itu, berdasarkan hasil penelitian diperoleh bahwa terdapat hubungan positif antara kepercayaan diri dalam mempelajari biologi dan rasa ingin tahu dengan motivasi berprestasi siswa.